Minocycline Improves the Efficacy of EGFR Inhibitor Therapy: A Hypothesis - Venniyoor, Ajit; Al Bahrani, Bassim (Frontiers in Oncology, 2016)
Skin rash is a side effect of drugs that inhibit Epithelial Growth Factor Receptor (EGFR) as a part of targeted therapy of cancer. It’s appearance and severity correlates with survival. Minocycline, an oral tetracycline antibiotic, is recommended as treatment (and increasingly, for prevention) of the rash, though infection is seen in only one-third of the patients. Minocycline has additional anti-cancer properties such as poly (ADP-ribose) polymerase (PARP) inhibition. It is proposed that such properties contribute to the efficacy of EGFR-inhibitors, and can also explain the positive correlation between grade of rash and survival as patients with higher grades of rash are more likely to receive minocycline. Early concurrent administration of minocycline is recommended in patients planned for EGFR therapy while awaiting trials proving this hypothesis.